PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BIMA - Tulnisah, Ika; Jaenab, Jaenab (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
The purpose of this study was to determine the effect of work motivation and physical work environment on the work productivity of employees at the Public Works and Spatial Planning Office of Bima Regency so that it can serve as input for the leadership of the Bima Regency Public Works and Spatial Planning Office. This research is quantitative research. This type of research is associative with the population used in this research, namely all employees at the Public Works and Spatial Planning Office of Bima Regency with a total of 204 employees based on work fields in the Public Works and Space Management Office of Bima Regency. The sample used in this study was ASN employees, totaling 89 employees. The sampling technique in this study used purposive sampling based on criteria. The research instrument used was a questionnaire with a Likert scale. The analytical tool used in this study uses multiple linear regression analysis using SPSS version 24. The results of this study are: 1) work motivation has no significant effect on employee work productivity in the Public Works and Spatial Planning Office of Bima Regency. 2) the physical work environment has a significant effect on employee work productivity at the Public Works and Spatial Planning Office of Bima Regency. 3) there is a significant simultaneous influence between work motivation and physical work environment on employee work productivity at the Public Works and Spatial Planning Office of Bima Regency.